Continuation of beta-blockers during prolonged dobutamine infusion in heart transplant–prioritised patients: A competing-risk analysis - Joao Manoel Rossi Neto; Victor Bemfica de Mello Mattos; Airton Salviano Sousa Junior; Marco Aurelio Finger; Raphael Machado Rossi; Plinio Jose Whitaker Wolf; Carlo Bonasso Filho; Flavia Potsch Camara Mattos Girard; Carolina Casadei dos Santos (PLoS ONE, 2026)
Background Patients awaiting heart transplantation (HT) frequently require prolonged continuous dobutamine infusion. Whether oral beta-blocker (BB) therapy should be maintained during this period remains controversial and poorly studied, particularly in the context of prolonged concomitant use. The impact of BB continuation on waiting-list outcomes in this specific scenario is unknown. Methods We conducted a retrospective single-centre cohort study including adult patients listed for HT who received ≥ 30 consecutive days of concomitant oral BB therapy and continuous intravenous dobutamine between January 2020 and December 2023. The index date was defined as the first day after completion of this 30-day period, identifying patients who had already demonstrated sustained haemodynamic tolerance to the combination. Patients were classified according to BB continuation or suspension after the index date. Competing-risk analyses were performed using inverse probability of treatment weighting (IPTW), Aalen–Johansen cumulative incidence functions, and Fine–Gray regression. Robustness was assessed through nonparametric bootstrapping (1,500 replications). Results Among 53 eligible patients (mean age 50.8 ± 11.9 years; 64% male), 29 underwent HT and 16 died before transplantation. After IPTW adjustment, BB continuation was associated with a higher cumulative incidence of HT at ≥ 270 days (61.1% vs 14.3%; p < 0.001) and a lower cumulative incidence of pre-transplant death (13.3% vs 68.7%; p < 0.001). Fine–Gray regression confirmed these associations: HT sHR 8.79 (95% bootstrap CI 2.66–54.31) and pre-transplant mortality sHR 0.077 (95% bootstrap CI 0.014–0.192). Results were consistent across four pre-specified sensitivity analyses. Conclusions This study evaluates outcomes in patients sustaining oral beta-blocker therapy during prolonged dobutamine infusion while awaiting heart transplantation, a clinical scenario with limited available data. BB continuation was associated with a higher probability of transplantation, with consistent direction across pre-specified sensitivity analyses. Given the small sample size and the potential for residual confounding by indication, these findings should be interpreted with caution and are best viewed as hypothesis-generating. They may help inform future research, particularly prospective studies in this setting.